A network maritime security approach to intelligence sharing in the IOR. Issue 3 (2nd September 2018) - Barnes, Jamal; Baldino, Daniel
ABSTRACT: The Indian Ocean Region (IOR) has become an area of critical strategic interest. It is also a region that contains a range of serious and evolving non-traditional security problems, including the problem of maritime terrorism. As a result, many IOR states have called for stronger pan-regional intelligence collaboration to assist in risk mitigation against such violent and destabilizing threats. This article explores the challenges involved in establishing an effective intelligence exchange network in a region characterized by mistrust, diversity and a lack of established security priorities and protocols. Building upon the success of the IOR's joint counter-piracy operations, it will argue that a less burdensome network-based approach is needed that can concentrate on issue-specific competencies and commonalties among states. In particular, while not without limitations, a more loosely coordinated and informal network governance approach can enhance opportunities to improve information-sharing to address common maritime security challenges, such as maritime terrorism, among IOR and extra-regional states.